STUDENTS’ PERCEPTION ON THE USE OF CODE-SWITCHING IN ENGLISH CLASSROOM - Yana Yana; Imam Fauzan Nugraha (PROJECT (Professional Journal of English Education), 2019)
This research aimed to investigate students’ perception on the use of code-switching in English classroom and to figure out its advantages for them in learning English. Qualitative research method was applied in this research. The participants of this research were 36 students of 10th grade in vocational high school in Cimahi. There were 36 students involved in the questionnaire and only 9 students involved in the interview session. The data from questionnaire were analyzed based on the theory of Cohen (2010) in (Rahmadani, 2016) to investigate the students’ perception and interview session to figure out its advantages for students in learning English. The result showed that (1) students showed their positive perceptions on the use of code-switching in English classroom being proven by 75% - 95% of the entire students and (2) students got several advantages from the use of code-switching in English classroom; enabling them to understand the material easily, helping them increase new vocabularies, helping them learn English faster, helping them understand every sentence in English easily, helping them take the main point of the learning, helping them avoid confusion, and making them comfort and confident in learning English.